Solved : How the World's Great Cities Are Fixing the Climate Crisis - Miller, David (University of Toronto Press, 2020)
If our planet is going to survive the climate crisis, we need to act rapidly. Taking cues from progressive cities around the world, including Los Angeles, New York, Toronto, Oslo, Shenzhen, and Sydney, this book is a summons to every city to make small but significant changes that can drastically reduce our carbon footprint. We cannot wait for national governments to agree on how to reduce greenhouse gas emissions and manage the average temperature rise to within 1.5 degrees. In Solved, David Miller argues that cities are taking action on climate change because they can - and because they must. Solved: How the World's Great Cities Are Fixing the Climate Crisis demonstrates that the initiatives cities have taken to control the climate crisis can make a real difference in reducing global emissions if implemented worldwide. By chronicling the stories of how cities have taken action to meet and exceed emissions targets laid out in the Paris Agreement, Miller empowers readers to fix the climate crisis. As much a "how to" guide for policymakers as a work for concerned citizens, Solved aims to inspire hope through its clear and factual analysis of what can be done - now, today - to mitigate our harmful emissions and pave the way to a 1.5-degree world.